Effects of different organic materials and reduced nitrogen fertilizer application on sorghum yield and soil nutrients - Rongsheng Wang; Chenguang Wang; Tao Liu; Yijia Chen; Bin Liu; Junbo Xiao; Yunmi Luo; Lei Chen (Scientific Reports)
Abstract Rapeseed and sorghum, important economic crops in China, generate abundant straw resources. However, studies examining the effects of straw return combined with reduced nitrogen fertilization on soil quality are still insufficient to meet the precise fertilization needs, necessitating further research. This study employed two treatments: rapeseed straw plus sorghum straw (LT) and rapeseed green manure plus sorghum straw (YGT) returned to the soil. Nitrogen was applied at three rates: 0%, 70% of the conventional amount (0.7CK) and the conventional fertilization (CK). Meanwhile, conventional fertilization was used as a control. Over three consecutive years, this experiment investigated the impact of these treatments on sorghum yield and soil nutrient properties, evaluating overall soil quality and individual soil fertility components. Straw return significantly improved soil quality, with enhancements ranging from 6.5 to 61.4% compared to the CK. The LT + 0.7CK and YGT + 0.7CK produced relatively higher yields, increasing by 10.9% and 10.49% respectively over the CK. Moreover, the comprehensive soil quality of these two treatments is also relatively high, and the comprehensive soil quality of both is at the same level. However, the absence of rapeseed yield in the YGT + 0.7CK treatment during the rapeseed season suggests that LT + 0.7CK is a more economically viable fertilization approach. Soil fertility evaluations indicated that the LT + 0.7CK treatment did not meet the third-level farmland nutrient standards for available potassium, organic matter, total phosphorus, and total potassium. Future fertilization strategies should continue incorporating organic fertilizers and further research to enhance soil phosphorus and potassium contents, thus improving fertilization schemes. This study provides valuable insights for the sustainable utilization of straw resources and the reduction of chemical fertilizers in the Yangtze River Basin.